Sudden Cardiac Deaths in a Metropolitan City of South India: A Prospective Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Many cases of sudden unexpected natural deaths occur in individuals without known medical diseases. Among them sudden cardiac death (SCD) remains an important worldwide public health problem. The epidemiology of SCD in India continues to be understudied. In this prospective an autopsy series was conducted at KIMS hospital Bangalore and various parameters were analysed, such as the frequency of SCDs among the autopsies conducted, the demographic profile and the causes for SCDs. Out of 760 autopsied victims during an 18-month study period, 88 cases were of sudden natural deaths. Among them 60 cases of sudden natural deaths were selected for the study based on purposive sampling. Among the 60 cases of sudden natural deaths, 38 cases (63.3%) were due to SCD. Maximum number of victims (47.3%) observed were in the age group of 41-50 years. Males constituted 92.1% of the total victims. Maximum cases were observed in the middle-class society (47.3%). Majority of the victims (78.9%) were from urban areas. Majority of the victims (73.6%) had a mixed diet. All the victims were habituated to smoking and alcoholism (50%) each. 39.57% of the study population were hypertensive and 31.57% were diabetics. Maximum number of victims (47.36%) succumbed to death within 6-12 hours of onset of terminal symptoms. Majority of the victims (63.15%) died due to occlusive coronary artery disease.
Keywords: Sudden cardiac death; India; Postmortem; Sudden natural deaths; Coronary artery disease; Mortality; Demography